996 Are KardiaMobile AliveCor devices useful in the diagnosis of children presenting with palpitations?. (17th August 2022) - Gray, Emma; Quirk, Jo; Davidson, Claire
Abstract : Aims: 1. To identify the main indication(s) for AliveCor provision in children (up to 18 years). 2. To assess whether children/families were able to obtain a recording using the AliveCor device during symptoms. 3. To evaluate whether AliveCor devices aided diagnosis in children presenting with palpitations. Methods: The AliveCor device is a pocket-sized heart monitor which links to a smartphone and obtains a 30 second single-lead ECG recording during patient symptoSince 2019 these have been used within the Yorkshire Congenital Heart Disease network to investigate children presenting with infrequent symptoms of palpitations (+/- chest pain). In total 48 devices were provided to children across Yorkshire between April 2019 and December 2021 by paediatric cardiologists and Paediatricians with Expertise in Cardiology (PECs). We analysed the use of AliveCor devices with data collected from the notes and clinic letters of these patients. Analysis focussed on indication for provision, rhythms recognised and final diagnosis and outcome of each patient. Results: Forty-eight patients aged 3-17 years were given an AliveCor device following an appointment in out-patient clinic with either a paediatric cardiologist or PEC. The majority of these patients had symptoms of palpitations requiring investigation: 67% (32/48). Within this cohort 11% also experienced chest pain. Other reasons for using the device as a diagnostic aid included chest pain alone (6%), collapse (4%), dizziness (8%) and breathlessness (4%). Of the patients presenting with palpitations AliveCor was useful in making a diagnosis in 56% (18/32). In all these cases one or more ECG recordings were obtained showing sinus rhythm/tachycardia (72%), ectopic beats (6%) or supraventricular tachycardia (SVT) (22%). This resulted in 13/32 (40%) of children presenting with palpitations being reassured and discharged, based on their AliveCor ECG recording. In 19% the device was not useful, with symptoms either too short-lived or families unable to capture a trace; in 25% lack of clear documentation made further analysis impossible. Conclusion: The results of this study suggest that AliveCor devices have a positive role in diagnosis of palpitations in children. The rapid generation of a single lead ECG trace during symptoms proved useful in the diagnosis of palpitations in 56% of patients, demonstrating their advantage in assessing infrequent symptoms in the community compared to current investigations, including 7-day tapes. By enabling a diagnosis to be made, 40% of children presenting with palpitations were able to be reassured and discharged, thus avoiding the need for further investigations or follow up, and relieving stress and anxiety for patients and family. Furthermore, in the small number of children diagnosed with SVT, AliveCor allowed discussions around further management and radio-frequency ablation in one patient.